Isokinetic peak torque in women with unilateral cumulative trauma disorders and healthy control subjects - Friedman, Paul J. (Archives of physical medicine and rehabilitation, 1998)
Objectives: To compare isokinetic peak torque in the symptomatic and asymptomatic limbs of women with lateral epicondyle or forearm pain due to cumulative trauma disorders (CTDs), and to compare peak torque in women with CTDs to peak torque in healthy women. Design: Case control comparison. Setting: Private occupational rehabilitation clinic and a sports science tertiary education center. Subjects: Women with CTDs involving one arm ( n = 17) and a convenience sample of healthy women ( n = 7) Intervention: Subjects performed isokinetic strength testing for wrist extension and flexion, wrist supination and pronation, and knee extension and flexion. Main Outcome Measures: Peak torque at 120°/sec on a Biodex isokinetic dynamometer. Results: Control subjects had significantly higher peak torque in wrist extension, flexion, supination, and pronation than CTD subjects on the symptomatic side. Control subjects also had significantly higher peak torque of wrist flexion, pronation, and supination than CTD subjects on the asymptomatic side; wrist extension was greater, but this did not reach significance. In addition, control subjects had significantly higher peak torque in knee extension and flexion than CTD subjects. CTD subjects had significantly greater left-right asymmetry in wrist extension torque than did control subjects. Conclusions: Isokinetic peak torque is diffusely reduced in women with unilateral CTDs compared with healthy control subjects, these differences occurring in symptomatic and asymptomatic limbs.